The Road User Perception of Municipal Road Deterioration: A Case Majalengka West Java - Dwiani, Nurmala; Irfan Rifai, Andri; Taufik, Mohamad; Handayani, Susanty (Journal Research of Social Science, Economics, and Management, 2024)
Municipal Roads are local infrastructure and serve as global routes for trade, tourism, and cultural exchange. Damage to roads is a topic of much urgent discussion in Indonesia. The aim of research on road damage in municipal roads, Majalengka, is to investigate the causes and impacts of road damage in the area. The research location to be carried out is Jalan Baribis in the Majalengka district. This research uses qualitative methods with perception analysis to study the various factors that cause damage to roads in the city of Majalengka and their Impact on society. When passing through Jalan Baribis, Majalengka, the respondents' data was divided into gender, vehicle used, and age. Based on the questionnaire results, the variable that received the highest importance value was the effect of road damage on two-wheeled vehicles and pedestrians, with an average value of 4.8. The variable that received the lowest importance value was road damage to public facility services, with an average value of 4.2. Meanwhile, the variable that received the highest satisfaction score was the effect of road damage on two-wheeled vehicles and pedestrians, with an average value of 2.6. On the other hand, the variable that got the lowest satisfaction score was the effect of road damage on heavy vehicles, with an average value of 2.14. From the research results, the level of importance of damage to road sections to road users has an average value of 4.48, which shows that repairing damaged road sections is very important.